O efeito do uso do fio dental na cárie dentária e na condição periodontal em adultos ao longo de 10 anos: um estudo de Coorte - Aquino, Icaro Santiago de (2024)
Dental caries and periodontal diseases constitute challenges for public health, whose biofilm represents the necessary common cause. Therefore, prevention is conditioned on the effective removal of biofilm, with the use of dental floss recommended alongside brushing. However, the effect of flossing on controlling these diseases is controversial. The study aimed to analyze the effect of flossing on tooth decay and periodontal condition over 10 years in adults in Sobral, Ceará, Brazil. This is a prospective cohort. The sample consisted of 260 adults aged 27 to 31 years, who participated in the 2012 and 2022 waves. Participants were examined based on the World Health Organization criteria. Data on sociodemographic conditions were collected through a structured script . The outcomes analyzed were tooth decay, tooth loss due to caries, gingival bleeding, dental calculus and periodontal pockets, according to concepts of “outcomewide epidemiology” and life course epidemiology. Initially, a cross-sectional analysis of dental flossing was carried out with the 2022 outcomes, applying Pearson’s chi-square test, and subsequent Poisson regression, with calculation of the prevalence ratio (PR) and adjustments for sex and family income . Therefore, a longitudinal analysis was carried out between 2012 and 2022, considering the trajectories of dental floss use: never used, sporadic use and always used, in which Pearson or Kruscal-Wallis chi-square was applied and, subsequently, the Poisson regression to estimate the relative risk (RR) between the analyzed outcomes and dental flossing trajectories, adjusted by sex and family income. In the 2022 wave, 33.8% of participants reported using dental floss. Of the oral health conditions, 69.2% had untreated cavities, 68.8% had dental calculus, 65.8% had teeth lost due to cavities and 64.2% had gingival bleeding and 12.7% had periodontal pockets. The average incidence of caries was 4.66 (SD=3.33), and of teeth lost due to caries was 1.22 (SD=1.59). Adults who flossed in 2022 had a lower prevalence of untreated tooth decay (PR = 0.72 [95% CI 0.59-0.89]), gingival bleeding (PR = 0.72 [95% CI 0.57 -0.91]) and dental calculus (PR = 0.79 [95% CI 0.64-0.96]). In the final longitudinal model, never having used dental floss was shown to be a risk factor for the incidence of teeth lost due to caries (RR = 1.98 [95% CI 1.25-3.13]), gingival bleeding (RR = 1 .49 [95% CI 1.10- 2.02]) and dental calculus (RR = 1.34 [95% CI 1.30-1.74]). Young adults who have never flossed for 10 years are more exposed to the emergence of oral problems, regardless of social class and gender. Its use is recommended as a measure to prevent and control oral health problems, such as cavities and periodontal diseases.